Bactérias de sisal (Agave sisalana P.) na produção de cebola - Rêgo, Maydara Thaylla Cavalcanti (2020)
The use of xerotolerant plant growth-promoting bacteria has advanced agricultural production under water-restricted conditions. In onion cultivation, this technique is still incipient but relevant to the semiarid region, as it increases water use efficiency. This study aimed to select bacteria associated with sisal with the potential to promote onion plant growth under different soil moisture levels. In the first experiment, bacteria were activated in TSA medium and used for seed microbiolization of the Fernanda hybrid. Twenty isolates were evaluated in a 20 × 2 factorial design (isolates × moisture levels: 25% and 50%), with three replications. After selection, six isolates and one control were tested in a second experiment. Germination was carried out in a B.O.D. chamber, with four replicates of 25 seeds, and emergence was conducted in a greenhouse, with four replicates of 36 seeds. For production, the Serena hybrid was used in a 7 × 3 factorial design (isolates × moisture levels: 50%, 75%, and 100%), with four replications and one plant per pot. The parameters evaluated were germination, emergence, number of leaves, shoot length, shoot dry mass, root dry mass, bulb length, bulb diameter, and fresh bulb mass. Isolates B1.9, C3.4, FO4.10, FO5.4, R1.4, and S1.9 promoted greater early growth of Fernanda onion plants under water deficit. In the Serena cultivar, there was no effect on germination or emergence; however, shoot dry mass, bulb diameter, and bulb length increased with bacterial application.